Assessing palliative care policies in Africa: Implication for paediatric palliative care - Ngowi, Epiphania (Department of Public Health and Family Medicine, 2021)
Around the world, there are millions of children who need palliative care from the moment they are diagnosed with life-threatening and life-limiting illnesses, yet very few children have access to palliative care services. In many African countries, where palliative care is still new, many children with chronic illnesses continue to experience needless pain and suffering. The World Health Assembly Resolution 67.19 made a clear call for governments around the world to implement palliative care policies. Such policies should support the “comprehensive strengthening of health systems to integrate evidence-based, costeffective and equitable palliative care services in the continuum of care, across all levels of care”. However, despite these frequent calls, no specific policies target the provision of paediatric palliative care in Africa. This dissertation consists of three parts. Part A is the study protocol, which consists of the introduction and the study methodology. The study is qualitative in nature and it adopted the Walt and Gilson framework for extraction of data and analysis of palliative care policies in Africa. The study used publicly available policy documents, which were identified and obtained from government websites, international agencies' websites and through communication with palliative care experts. An excel spreadsheet was used to extract data, which was analysed thematically. Part B is a literature review of available published and unpublished work pertaining to paediatric palliative care in Africa. It provides the historical background of palliative care and defines palliative care and paediatric palliative care as well as exploring the general literature on paediatric palliative care, and the evidence on the existence of palliative care policies in Africa. Part C is a journal manuscript. It follows the structure and guidelines of the journal of the Health Policy and Planning. The manuscript begins with introduction and the study methods. Further, the study used publicly available policy documents on palliative care in Africa published from 2002 until 2018. An appropriate conceptual framework was chosen, and the results of the policy analysis are provided and followed by the discussion section and conclusions. The study findings indicate that few palliative care policies exist in Africa, and children's palliative care needs are not adequately included and addressed. The findings further show that there was no single policy targeting paediatric palliative care, and children were included among the larger population. As such, palliative care needs were not sufficiently addressed. Only three policies (South Africa, Zimbabwe, and Malawi) clearly address paediatric palliative care needs. The study, therefore, argues that for children with life threatening and life-limiting conditions to be free from pain, African governments need to formulate specific policies that will guide the provision of paediatric palliative care. This study is likely contribute to policy making processes, acts as a reference document for academics and students and provides an advocacy tool for activists, nongovernmental organizations (NGOs), and civil society organizations (CSOs) working on children's welfare and human rights issues more broadly. Further, the findings of the study may contribute to formulating specific palliative care policies for children, particularly in African countries that lack such policies.